Position Summary: Hinting for Goodness' Sake - Petrou, David; Narayanan, Dushyanth (Proceedings of the 8th Workshop on Hot Topics in Operating Systems (HotOS-VIII), 2001)
Modern operating systems and adaptive applications offer an overwhelming number of parameters affecting application latency, throughput, image resolution, audio quality, and so on. We are designing a system to automatically tune resource allocation and application parameters at runtime, with the aim of maximizing user happiness or goodness.